2021
DOI: 10.48550/arxiv.2110.09992
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ERQA: Edge-Restoration Quality Assessment for Video Super-Resolution

Abstract: Despite the growing popularity of video super-resolution (VSR), there is still no good way to assess the quality of the restored details in upscaled frames. Some SR methods may produce the wrong digit or an entirely different face. Whether a method's results are trustworthy depends on how well it restores truthful details. Image super-resolution can use natural distributions to produce a high-resolution image that is only somewhat similar to the real one. VSR enables exploration of additional information in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The FEL criteria are based on edge detection in real-world images and do not require a ground truth image. In work [ 37 ], a method for evaluating the quality of detail restoration in video super-resolution was proposed, called edge restoration quality assessment (ERQA), which was also based on edge detection. While this work showed that edge restoration is critical for human perception of detail restoration, their method required ground truth images.…”
Section: Deep Learning-based Image Reconstructionmentioning
confidence: 99%
“…The FEL criteria are based on edge detection in real-world images and do not require a ground truth image. In work [ 37 ], a method for evaluating the quality of detail restoration in video super-resolution was proposed, called edge restoration quality assessment (ERQA), which was also based on edge detection. While this work showed that edge restoration is critical for human perception of detail restoration, their method required ground truth images.…”
Section: Deep Learning-based Image Reconstructionmentioning
confidence: 99%
“…The ERQA metric [13] assesses images in terms of detail restoration. To do so, it detaches object edges and matches them with their counterparts in the reference image.…”
Section: B Super-resolution Quality Metricsmentioning
confidence: 99%
“…After super-resolving videos, we calculated the following objective-video-quality metrics on the results: PSNR, MS-SSIM [26], VMAF [2], LPIPS [32], and ERQA [13]. We ranked the SR methods by calculating BSQ-rate (bitrate-forthe-same-quality rate) [33] for each SR+codec pair relative to base codec performance, where the base codec is the one we used to compress low-resolution video.…”
Section: Objective-quality Estimationmentioning
confidence: 99%
See 1 more Smart Citation